2015
DOI: 10.1038/nphys3343
|View full text |Cite
|
Sign up to set email alerts
|

Wheeler's delayed-choice gedanken experiment with a single atom

Abstract: The wave-particle dual nature of light and matter and the fact that the choice of measurement determines which one of these two seemingly incompatible behaviours we observe are examples of the counterintuitive features of quantum mechanics. They are illustrated by Wheeler's famous 'delayedchoice' experiment 1 , recently demonstrated in a single-photon experiment 2 . Here, we use a single ultracold metastable helium atom in a Mach-Zehnder interferometer to create an atomic analogue of Wheeler's original proposa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
74
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 126 publications
(78 citation statements)
references
References 27 publications
3
74
0
1
Order By: Relevance
“…An experiment by scientists at the Australian National University, using helium atoms scattered by light, has blurred the distinction between past, present and future [25]. In these studies, cause and effect were reversed.…”
mentioning
confidence: 74%
“…An experiment by scientists at the Australian National University, using helium atoms scattered by light, has blurred the distinction between past, present and future [25]. In these studies, cause and effect were reversed.…”
mentioning
confidence: 74%
“…More recent experiments have again contradicted non-contextuality and confirmed that, unlike what one would expect if the world were separate or distinct from mind, the observed properties of the world indeed cannot be said to exist prior to being observed (Lapkiewicz et al 2011;Manning et al 2015). For all intents and purposes, the world we perceive is a product of observation.…”
Section: The Ontological Status Of the Worldmentioning
confidence: 92%
“…With all the specific attributes of photoelectron spin control, however, repeating such a success would be expremely difficult. Furthermore, we could have discussed far simpler examples of quantum erasure [103,105,145], delayed choice [102,[146][147][148], and quantum delayed choice [51,78,79], based on established technology like linear quantum optics that is used routinely in applications of quantum information theory. Indeed, we do not propose photoelectron spin control to show that quantum erasure and quantum delayed choice are possible or to provide further evidence that nature violates local realism.…”
Section: Facing the Loopholesmentioning
confidence: 99%